2015
DOI: 10.1021/jf506110y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Mechanism of Ginseng Saponin Metabolite Rh3 in Lipopolysaccharide-Stimulated Microglia: Critical Role of 5′-Adenosine Monophosphate-Activated Protein Kinase Signaling Pathway

Abstract: Ginsenoside Rh3 is a bacterial metabolite of Rg5, which is the main constituent of heat-processed ginseng. The present study was undertaken to examine the anti-inflammatory effect of ginsenoside Rh3 in lipopolysaccharide (LPS)-stimulated microglia. Rh3 inhibits the expressions of inducible nitric oxide synthase (iNOS) and proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6, at mRNA and protein levels, while Rh3 enhanced anti-inflammatory hemeoxygenase-1 expression. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Interestingly, recent studies have also revealed that inflammatory defenses can be regulated by AMPK, which does not directly target NF‐κB but rather mediates the inhibition of NF‐κB by modulating SIRT1, PGC‐1α, p53, or FoxO . Rh3 inhibits neuroinflammation accompanied by microglial activation at least partially by upregulating AMPK/SIRT1 and inhibiting the phosphorylation of its downstream kinases PI3K/Akt and JAK1/STAT1; this is eventually associated with the inhibition of NF‐κB and enhancement of Nrf2 pathways . Rg1 was found to alleviate inflammation‐based liver damage caused by CCl4, which was attributed to the stimulation of AMPK/SIRT1 and suppression of the NF‐κB pathway …”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 97%
“…Interestingly, recent studies have also revealed that inflammatory defenses can be regulated by AMPK, which does not directly target NF‐κB but rather mediates the inhibition of NF‐κB by modulating SIRT1, PGC‐1α, p53, or FoxO . Rh3 inhibits neuroinflammation accompanied by microglial activation at least partially by upregulating AMPK/SIRT1 and inhibiting the phosphorylation of its downstream kinases PI3K/Akt and JAK1/STAT1; this is eventually associated with the inhibition of NF‐κB and enhancement of Nrf2 pathways . Rg1 was found to alleviate inflammation‐based liver damage caused by CCl4, which was attributed to the stimulation of AMPK/SIRT1 and suppression of the NF‐κB pathway …”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 97%
“…Recent studies show that AMPK regulates both energy homeostasis and inflammatory defense [1113]. Activation of AMPK inhibits ATP-consuming anabolic processes (such as protein translation) mainly via inhibiting mammalian target of rapamycin (mTOR) signaling [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, AMPK activation inhibits lipopolysaccharide (LPS)-induced pro-inflammatory cytokines expression by modulating NF-κB in primary rat microglia [16]. AMPK activation also inhibits the expression of pro-inflammatory mediators in the cerebral cortex of LPS-injected rats [11]. Thus, AMPK may be an interesting target for neuroprotective drugs in inflammatory conditions, such as morphine tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…3B). MAPKs play critical roles in cell proliferation, differentiation, and apoptosis [23], [24]. Therefore, these results demonstrate that inhibition of the MAPKs-apoptosis signaling cascade plays a critical role in mediating the renoprotective effect of ginsenoside Rh3.…”
Section: Resultsmentioning
confidence: 62%